767 NEVER TOO LATE TO SHOW-UP: A RARE CASE OF PLATYPNEA-ORTHODEOXIA SYNDROME. (15th December 2022) - Gioscia, Rocco; Verdoia, Monica; Rognoni, Andrea
Abstract: Patient presentation . We present the case of an 85-years old woman, hypercholesterolemic, with a previous history of microvascular angina treated with nitrates, ASA and ranolazine. She presented in our emergency department for repeated episodes of seizure and "drop attacks" and she underwent neurological and cardiological evaluation. ECG showed sinus tachycardia, 110/min, left anterior hemiblock. Transthoracic echocardiogram was normal. Head CT-scan and cerebral magnetic resonance documented mild hyperintense areas in the subcortical part of white matter suggestive for chronic cerebrovascular disease. Carotid Doppler was negative for significant stenosis. Thus, suspecting an unexplained syncope, she underwent loop recorder implantation. One month later she was admitted to the emergency room for dysarthria, left hemiparesis and ataxia, that completely regressed after 24-hours, posing the diagnosis of transient ischemic stroke. Physical examination was normal. During in-hospital stay, the patient progressively developed dyspnoea and oxygen desaturation (SpO2 < 90%). Initial work-up . Due to oxygen desaturation non-invasive ventilation with Venturi mask (60%) was started. Blood tests were normal. The arterial blood gas analysis in Venturi mask showed: pH 7.47, pCO2 48 mmHg, pO2 136 mmHg, P/F 226. Despite non-invasive ventilation with Venturi mask, P/F remained low and so continuous positive airway pressure (CPAP) was started. A repeated echocardiogram showed a mild reduction of ejection fraction (45-50%) due to hypokinesia of the septum, secondary to right ventricular overload and compression. Pulmonary embolism was excluded by angio-CT. Medical management with vasodilators and diuretics finally allowed to wean off the non-invasive ventilation, still maintaining oxygen support with nasal cannulas. However, surprisingly, the mobilization of the patient in a sitting position resulted impossible, due to the occurrence of sudden desaturation. Diagnosis and Management . Suspecting a manifestation of platypnea-orthodeoxia syndrome (POS) a transoesophageal echocardiogram was performed. It revealed a wide patent foramen ovale (PFO), maximum diameter 1.5 cm, with a baseline mild right-to-left shunt, confirmed with sonicated contrast, that increased in the sitting position. Therefore, the diagnosis of POS syndrome and paradoxical cerebral embolization was posed. Elective PFO closure with the percutaneous positioning of an atrial septal defect (ASD) Occluder n.15 was successfully performed. Conclusions: The platypnea-orthodeoxia syndrome is a rare cause of hypoxemia. The most common structural abnormality associated with this syndrome is the PFO, which can remain asymptomatic for decades. A shift in the relationship between right-and left intra-cardiac pressures, a change in the anatomy of the adjoining structures with age, stretching the atrial septum and favouring the blood inflow into the PFO (as ascending aorta dilatation or Thoracic Kyphosis) can lead to POS. The closure of the atrial defect is generally resolutive. However, the heterogeneous clinical presentations, the rarity of the disease and the confounding role of comorbidities can often result misleading, especially in advanced age.